2012
DOI: 10.1093/ehjci/jes017
|View full text |Cite
|
Sign up to set email alerts
|

Left superior vena cava: revisited

Abstract: The persistence of a left-sided superior vena cava is the most common variant of systemic venous drainage. Increased utility of cardiac imaging, in particular cross-sectional techniques such as computed tomography and magnetic resonance (MR), will result in increased detection of the anomaly and its variants. Whilst in the typical form it is often haemodynamically insignificant, its discovery may have clinical significance nonetheless, and its mimics require exclusion. During cardiac development the anomaly re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
84
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(84 citation statements)
references
References 29 publications
0
84
0
Order By: Relevance
“…The left anterior cardinal vein connects caudally with the duct of Cuvier-later the coronary sinus (CS)- and with the subclavian/innominate vein in the cephalad direction (Figure 1A). 5 It may remain open as the normal variant of persistent left superior vena cava, but most commonly only its intracardiac portion remains patent as the VOM (also known as oblique vein of the left atrium (LA)), connected with the CS at the level of the valve of Vieussens. In the adult, the LOM contains portions of the VOM, a myocardial sleeve (the Marshall bundle [MB]), and autonomic nerves 6 .…”
Section: Anatomy and Physiological Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…The left anterior cardinal vein connects caudally with the duct of Cuvier-later the coronary sinus (CS)- and with the subclavian/innominate vein in the cephalad direction (Figure 1A). 5 It may remain open as the normal variant of persistent left superior vena cava, but most commonly only its intracardiac portion remains patent as the VOM (also known as oblique vein of the left atrium (LA)), connected with the CS at the level of the valve of Vieussens. In the adult, the LOM contains portions of the VOM, a myocardial sleeve (the Marshall bundle [MB]), and autonomic nerves 6 .…”
Section: Anatomy and Physiological Functionmentioning
confidence: 99%
“…5 Even if the ligament is patent as the VOM, whether the VOM provides any venous drainage function to the LA was unclear. We showed that the VOM serves a true venous function that communicated with the underlying myocardium and is therefore a viable vascular route for the delivery of therapeutic agents to the LA myocardium.…”
Section: Vom Ethanol Infusionmentioning
confidence: 99%
“…[137][138][139][140][141][142] Systemic venous anomalies are also well visualized by cardiovascular CT. [143][144][145] Cardiovascular CT has also been shown to accurately visualize congenital aortic anomalies including interrupted aortic arch and aortic coarctation in both pediatric and adult patients. [146][147][148][149][150][151][152][153] It is particularly useful for evaluation of the aortic arch after endovascular intervention (stent or stent graft) where aneurysm, aortic wall injury or recurrent arch obstruction are relatively common.…”
Section: Patientsmentioning
confidence: 99%
“…Persistent left-sided superior vena cava (PLS-SVC) is the most common venous mediastinal variant with a prevalence estimated approximately of 0.3-0.5% in the general population [1,2] and of 4% in patients with congenital heart diseases [3]. In 90% of cases, the superior vena cava (SVC) is bilateral.…”
Section: Introductionmentioning
confidence: 99%